77 Opioid overdose death in wales from 2012 to 2015: a linked data autopsy study. (16th April 2018) - Jones, M; Snooks, H; Watkins, A; Fuller, G
Abstract : We performed a retrospective autopsy study to better understand factors associated with opioid poisoning death. Using anonymised linked data we describe demographic characteristics, emergency service utilisation, and clinical presentation prior to death. Method: Decedents of opioid poisoning in Wales in 2015 were identified from Office of National Statistics (ONS) mortality data and their records linked with the Emergency Department data. Results: Age at death ranged 18 to 78 years, with a mean of 42. Average male age was 41 and average female age was 44. 76% of decedents were men (n=98/112). 87% of decedents (n=112/129) attended the emergency department in the three years prior to death; n=89 in the previous year, 99 in the previous two years and 112 in the previous three years. 84% of male and 93% of female decedents attended the ED in the three years prior to death. There were 665 attendances, and half involved conveyance by ambulance. Attendances per individual ranged from 1 to 60, with over half of decedents attending more than three times. Diagnostic codes were mostly missing or non-specific, with only 6.5% of attendances representing 27 decedents, coded as drug related. Conclusion: Matching previously published data, we found that fatal opioid poisoning is preceded by a period of high emergency health service utilisation. On average decedents were in their fifth decade and more likely to be male than female. Attendances varied widely, with men less likely to attend than women. Conflict of interest: None Funding: PRIME Centre Wales